Aminoguanidine prevents testicular damage-induced-2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in male rats - Oguz, F.; Ciftci, O.; Aydin, M.; Timurkaan, N.; Beytur, A.; Altintas, R.; Parlakpinar, H. (Wiley, 2013)
In this study, it was aimed to determinate protective effects of aminoguanidine (AG) against reproductive toxicity caused by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), an environmental contaminant. Thirty-two rats were equally divided into four groups; the first group was kept as control and given corn oil as carrier. In second and third groups, TCDD and AG were orally administered at the dose of 2 mu k g(-1) per week and 100 mg kg(-1) per day for 45 days, respectively. In fourth group, TCDD and AG were given together at the same doses. Although TCDD significantly increased the formation of TBARS, it caused a significant decline in the levels of GSH, CAT, GPx and SOD in rats. On the other hand, AG, given together TCDD, reversed TCDD effects on TBARS SOD, GSH, GPx and CAT. In addition, sperm characteristics negatively affected and histopathological deformation occurred with TCDD exposure. However, AG treatment partly prevented these toxic effects of TCDD on spermatological parameters and histopathological changes. In conclusion, TCDD exposure induces testicular damage (oxidative stress, histopathological damage and sperm parameters), and AG treatment reversed TCDD-induced testicular damage in rats. Thus, AG may be useful for the prevention and treatment of TCDD-induced male infertility problems.
Keywords: Aminoguanidine; oxidative damage; sperm quality; testicular damage; 2,3,7,8-tetrachlorodibenzo-p-dioxin